Understanding the motives behind the consumption of organic products in North Portugal: a focus group study - Penalba-Sánchez, Lucía; Di-Gregorio, Elisa; Claro, Raquel; Pinto, Mafalda; Pinto, Elisabete; Oliveira-Silva, Patrícia (Frontiers in Sustainable Food Systems, 2023)
Introduction The soil is a non-renewable and essential resource for life on our planet. Considering the widespread fast pace of soil degradation and erosion, it is urgent to protect it by enacting pro-environmental behaviors. Consumers’ massive purchase and consumption of organic products is a powerful way to encourage farmers to apply sustainable soil practices. Unfortunately, there is a lack of studies in Portugal explaining the increased interest but low consumption of organic products. Methods Here, the relationship between (a) intrinsic motivations, extrinsic motivations, knowledge, and self-perception of control regarding pro-environmental behaviors, and (b) consumption of organic products and other related pro-environmental behaviors was explored. To do so, two semi-structured interview focus groups (n = 15 participants) were conducted. Results Organic product purchase and consumption seem to be driven by intrinsic motivations such as health or environmental concerns. External aspects such as labels and price as well, as personal, and psychological elements like knowledge and self-control, may be attenuating or strengthening the behavior. These findings should be validated in quantitative studies.